PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF PENDIDIKAN AGAMA ISLAM MATERI TATA CARA SHOLAT UNTUK KELAS II SEKOLAH DASAR - Zinnurain, Zinnurain (Jurnal Paedagogy, 2020)
This study aims to: (1) produce multimedia Islamic Studies learning materials for prayer procedures that are suitable for use for grade II elementary school students in terms of material, learning, display and programming aspects; (2) knowing student responses; and (3) knowing its effectiveness in learning. This research is research and development (R&D) which includes the following stages: (1) needs analysis, (2) learning design, (3) product development, and (4) evaluation. The subjects in this study were 29 grade II students of SD Negeri Samirono, Sleman, Yogyakarta. The results of the study are as follows. (1) The multimedia product of PAI learning, this prayer procedure material is feasible or valid. The assessment of multimedia learning from the aspects of material, learning, display and programming is categorized as very good. (2) Student response to multimedia that was developed was very good. (3) The effectiveness of the developed learning multimedia is in the "high" category. These results indicate that the developed multimedia learning Islamic religious education materials for prayer procedures can be used as a teaching material in the learning process of Islamic religious education in grade II of elementary schools.